Contributions to Healthcare Cost and Utilization of Wisconsin Medicare Part A Enrollees through 2018 - Goodrich, Ryan (My University, 2010)
With the aging of the baby boom generation, the percentage of the population that is 65 and older is projected to be 20% by the year 2030. It is well-known that, on average, older individuals utilize healthcare more than younger individuals. Mix these two trends with the rapid rise in healthcare costs in recent years and it is not difficult to see that budget issues are looming in the not-so-distant future. The purpose of our research was to project the healthcare costs of Medicare enrollees in Wisconsin and to seek to understand how much of these costs are linked to lifestyle choices.
Color poster with text and graphs.
Keywords: Medicare--Costs--Wisconsin; Medical care, Cost of--Health aspects; Medical care, Cost of--Sociological aspects; Medical care, Cost of--Wisconsin; Health behavior--Economic aspects--Wisconsin; Lifestyles--Health aspects--Wisconsin; Posters